Pemberian Pupuk Organik Cair terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) di Polibag - Tribuyana, Nova; Hanan, Ridwan; Yuliantina, Yuliantina (Jurnal Agroekoteknologi, 2025)
Horticultural plants are still a favorite in agricultural activities, apart from the cultivation method which is not too difficult, they also have a short production life. Pakcoy plants are plants that are rich in fiber, contain lots of nutrients and are a type of vegetable that is easy to cultivate. The pak choy plant is a type of vegetable from the mustard plant variety whose leaves are used. Interest in the use of this type of vegetable is increasing day by day, so to be able to get maximum production it is necessary to add fertilizer as an additional nutrient. This research aims to determine the effect of growth and production of pakchoy mustard greens (Brassica rapa L.) in polybags with the addition of liquid organic fertilizer (POC). Carried out in the experimental garden of the Faculty of Agriculture, Tridinanti University, Semambu Village, Ogan Ilir District, South Sumatra using a Randomized Block Design with 6 (six) treatments and 4 (four) replications consisting of P0 = Without application of liquid organic fertilizer (0 ml/l water. ), P1 = Providing 2 ml/l of liquid organic fertilizer (POC), P2 = Providing 4 ml/l of liquid organic fertilizer (POC), P3 = Providing 6 ml/l of liquid organic fertilizer (POC), P4 = Providing 8 ml/l of liquid organic fertilizer (POC), and P5 = Providing 10 ml/l of liquid organic fertilizer (POC) of water. Each experimental unit consisted of 10 plants, 3 (three) sample plants were taken as samples. The results of the research showed that P4 treatment of 8 ml POC was the best treatment for the parameters of plant height (cm), number of leaves (strands), plant fresh weight (g) and plant dry weight.